Framework for probabilistic tsunami hazard assessment considering the effects of sea-level rise due to climate change. (January 2022) - Alhamid, Abdul Kadir; Akiyama, Mitsuyoshi; Ishibashi, Hiroki; Aoki, Koki; Koshimura, Shunichi; Frangopol, Dan M.
Highlights: A framework for incorporating uncertainties associated with sea-level rise in probabilistic tsunami hazard assessments (PTHAs) is established. A practical approach for probabilistic sea-level rise hazard assessment is provided by utilizing the available climate models and data. Tsunami hazard curves considering the effects of sea-level rise are estimated based on the total probability theorem. Neglecting the effects of sea-level rise in a low-lying coastal plain can significantly underestimate tsunami hazards. Abstract: Sea-level rise due to climate change could significantly exacerbate tsunami disasters since the sea level is a critical parameter affecting the intensity of tsunamis. Considering the impacts of future climate change on the ocean, a method to consider the effects of sea-level rise on the tsunami hazard intensity is needed to precisely predict future tsunami disasters. This paper presents a novel framework for probabilistic tsunami hazard assessment, considering the sea-level rise and associated uncertainties. A probabilistic assessment of the sea-level rise hazard is performed using the available data and climate models considering several climate change emission scenarios. Conditional tsunami hazard curves are estimated by conducting tsunami propagation simulations given a sea-level rise while considering the uncertainties associated with fault movement (i.e., rake angles and average stress drops). Radial-basis-function-based surrogate models and quasi-Monte-Carlo simulations are employed to obtain tsunami hazard curves. Finally, the tsunami hazard curves considering the effects of sea-level rise are estimated by convolving the corresponding regional sea-level rise hazard with the conditional tsunami hazard curves based on the total probability theorem. An illustrative example is provided, in which the proposed framework is applied to several municipalities in the Mie Prefecture of Japan that would be affected by tsunamis during the anticipated Nankai-Tonankai earthquake. The effects of sea-level rise on the tsunami hazard intensities associated with the municipalities are discussed.